2022
DOI: 10.1684/epd.2022.1452
|View full text |Cite
|
Sign up to set email alerts
|

Koolen‐de Vries syndrome associated with continuous spike‐wave in sleep

Abstract: Koolen-de Vries syndrome (KdVS) is a genetic condition caused by 17q21.31 microdeletions or pathogenic variants in KANSL1. Affected patients most commonly exhibit some or all of the following: neonatal hypotonia, developmental impairment, facial dysmorphic features, and congenital malformations. Epilepsy occurs in approximately half, often with phenotypes on the epilepsyaphasia spectrum. We describe six children with KdVS found to have continuous spike-wave in sleep (CSWS) on EEG, four of whom were diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Two cases underwent a KD variation, and for both, a clinical improvement was reported. The authors concluded that a prolonged EEG during sleep should be performed in all KdVS children showing a regression or plateau of development, especially when there is a previous history of seizures [263]. Mowat-Wilson syndrome is a rare genetic disease due to a heterozygous deletion or function loss of the ZEB2 gene located on chromosome 2.…”
Section: Etiopathogenetic Factors Of Csws (Including Eses and Lks)mentioning
confidence: 99%
“…Two cases underwent a KD variation, and for both, a clinical improvement was reported. The authors concluded that a prolonged EEG during sleep should be performed in all KdVS children showing a regression or plateau of development, especially when there is a previous history of seizures [263]. Mowat-Wilson syndrome is a rare genetic disease due to a heterozygous deletion or function loss of the ZEB2 gene located on chromosome 2.…”
Section: Etiopathogenetic Factors Of Csws (Including Eses and Lks)mentioning
confidence: 99%
“…Koolen-de Vries Syndrome (KdVS) is a multi-system disorder due to a de novo, heterozygous 17q21.31 deletion or pathogenic variant in the KANSL1 gene. 1 KdVS is characterized by neonatal hypotonia, developmental delay, intellectual disability, speech difficulties, 2 epilepsy, 3 , 4 congenital abnormalities of the heart and/or urogenital system, respiratory problems, ophthalmic issues, facial dysmorphism and musculoskeletal problems. 5 , 6 Some children with KdVS are born with one or more congenital abnormalities, 5 and a large portion present with neonatal hypotonia and feeding problems.…”
Section: Introductionmentioning
confidence: 99%